2002
DOI: 10.1023/a:1021034028295
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Lactulose has been proposed to be beneficial in treating inflammatory bowel disease (IBD). The hypothesis is based on the prebiotic potential of lactulose. A practical approach to testing its usefulness is to determine colonic adaptation to tolerable doses in patients with IBD. Our objective was to determine if a 3-week course of lactulose will decrease BH2 and symptoms in response to an acute lactulose challenge test in control subjects and IBD patients. The design was a prospective cohort study. Subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However ability to adapt to lactose in IBD is unclear and there are no formal trials. Using lactulose, a disaccharide with similar properties to lactose failed to show adaptation compared with healthy controls [ 79 ]. Pironi et al however may have detected microbial adaptation since despite increased LM status only 8 % of CD patients were also LI [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However ability to adapt to lactose in IBD is unclear and there are no formal trials. Using lactulose, a disaccharide with similar properties to lactose failed to show adaptation compared with healthy controls [ 79 ]. Pironi et al however may have detected microbial adaptation since despite increased LM status only 8 % of CD patients were also LI [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hafer et al conducted a pilot study on 31 subjects suffering from IBD (both UC and CD) and found that a 10 g lactulose administration did not show any beneficial effect, except for an improvement of the clinical symptoms and the quality of life of patients with CU, without significant modifications at the endoscopic level [142]. As Fellerman et al reported, this discrepancy could be related to a defensin deficiency in IBD, which is reversible only in UC and not in CD patients, following lactulose administration [143,144].…”
Section: Prebiotics and Gastrointestinal Disordersmentioning
confidence: 95%
“…This could be due to overt or subtle small bowel involvement. Furthermore, adaptation to the disaccharide lactulose was unsuccessful in patients with Crohn’s disease compared with healthy controls [ 153 ].This suggests a reason also why Crohn’s patients may have more difficulty with DFs containing lactose.…”
Section: Effects Of Dairy Foods On Diseasesmentioning
confidence: 99%